How institutions governing the economic middle in food provisioning are reinforced: The case of an agri-food cluster in northern Uganda. (December 2020) - Schoonhoven-Speijer, Mirjam; Vellema, Sietze
Highlights: A diverse ensemble of intermediary traders jointly shape access to food. The food cluster is recognized internally and externally as an institution for trade. A practice-oriented approach demonstrates how institutions are self-reinforced. Assembling a variety of practices is a condition for consolidating the cluster. An institutionally viable food cluster enables access to food in rural settings.